2019
DOI: 10.1016/j.amepre.2019.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Black–White Disparities in Preterm Birth: Geographic, Social, and Health Determinants

Abstract: Introduction: Reducing racial/ethnic disparities in preterm birth is a priority for U.S. public health programs. The study objective was to quantify the relative contribution of geographic, sociodemographic, and health determinants to the black, non-Hispanic and white, non-Hispanic preterm birth disparity. Methods: Cross-sectional 2016 U.S. birth certificate data (analyzed in 2018−2019) were used. Black−white differences in covariate distributions and preterm birth and very preterm birth rates were examined. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
62
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 44 publications
6
62
0
5
Order By: Relevance
“…It became well recognized that Socio-demographic and preconception/prenatal health factors do affect preterm birth rates [7][8][9][10][11]. The Peristat registry records all preterm births in the state of Qatar.…”
Section: Discussionmentioning
confidence: 99%
“…It became well recognized that Socio-demographic and preconception/prenatal health factors do affect preterm birth rates [7][8][9][10][11]. The Peristat registry records all preterm births in the state of Qatar.…”
Section: Discussionmentioning
confidence: 99%
“…Work in this field should also recognize and acknowledge the historical legacies of oppression that have intergenerational impacts on health and wellness, even before a child is born (Owens & Fett, 2019). Both policies and practices are needed to address these health disparities in birth outcomes that appear to be growing in our current sociopolitical context (e.g., Thoma et al, 2019), especially during this time of increased police brutality targeting African Americans (Edwards, Lee, & Esposito, 2019) and during the COVID‐19 pandemic, which affects African Americans disproportionately, largely because of our history and current practices of systemic racism (Devakumar, Shannon, Bhopal, & Abubakar., 2020). In this article, we sought to shed light on a major gap in our understanding of the biological embedding of chronic stress that is unique to people of color in efforts to reduce the major health disparities in marginalized communities.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic and ethnic‐racial disparities are a major risk for prematurity 12 . Studies have shown that non‐Hispanic Black women are 2.5 times more likely to have preterm birth vs White women 13 . The dynamics and interplay between these three risk factors (preterm birth, non‐White race, and government insurance) are challenging, and the coexistence of these factors is not uncommon.…”
Section: Discussionmentioning
confidence: 99%